MAN DOMINATION AND DOMESTIC VIOLENCE DESCRIBED IN SWEAT BY ZORA NEALE HURSTON - Yogi Ario Setiawan; Agnes Widyaningrum (Universitas Stikubank (UNISBANK) Semarang, 2020)
This study is a descriptive qualitative study, focused in discussing the domestic violence and man domination that are potrayed in Zora Neale Hurston “Sweat” in 1926. This story presents a woman who is trapped in a bad marriage. This story has protagonist character and antagonist character. The woman in this story is protagonist, and the man is antagonist. The woman becomes victim of domestic violence. She has to struggle to provide her living. As a part of feminism study, the researcher uses feminism approach. It focuses on the explanation on how the character gets violence using Simone de Beauvoir theory “The Second Sex” (1949) which is applied to analyze this research paper. The aim of this research is to analyze the problem of domestic violence towards woman. The researcher shows the domestic violence happened in that era, and men are dominant because of the social construct build to make men are powerful. Domestic violence and man domination in the early 20th century can truly be seen in Zora Neale Hurston story.